2014
DOI: 10.1111/papr.12227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High‐voltage‐ with Standard‐voltage Pulsed Radiofrequency of Gasserian Ganglion in the Treatment of Idiopathic Trigeminal Neuralgia

Abstract: Although pulsed radiofrequency treatment (PRFT) has been used to treat trigeminal neuralgia (TN) safely, satisfactory improvement is lacking. Recently, much attention has been paid to the PRFT dose and intra-operative parameters. It has been reported that high-voltage PRFT could significantly reduce discogenic pain. However, there is no study investigating the effects of high-voltage PRFT on TN. The aim of this prospective, randomized, double-blinded study was to evaluate the efficacy and safety of high-voltag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 26 publications
7
64
0
Order By: Relevance
“…Therefore, the study results could only suggest that PRF might have treatment effects on idiopathic supraorbital neuralgia patients. Consistent with previous treatment of trigeminal neuralgia or extracranial neuralgia of the trigeminal nerve using PRF, 8,11,14 treatment of supraorbital neuralgia using PRF did not immediately achieve satisfactory efficacy; the possible cause was the time course for effect of PRF. In this study, the average response time of approximately 7 days showed that PRF could take some time for full effect.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Therefore, the study results could only suggest that PRF might have treatment effects on idiopathic supraorbital neuralgia patients. Consistent with previous treatment of trigeminal neuralgia or extracranial neuralgia of the trigeminal nerve using PRF, 8,11,14 treatment of supraorbital neuralgia using PRF did not immediately achieve satisfactory efficacy; the possible cause was the time course for effect of PRF. In this study, the average response time of approximately 7 days showed that PRF could take some time for full effect.…”
Section: Discussionsupporting
confidence: 65%
“…Several recent studies have noted that the PRF treatment of the Gasserian ganglion is a minimally invasive, safe, and effective interventional treatment choice for trigeminal neuralgia patients. [7][8][9][10] Several recent reports have shown that treatment of extracranial neuralgia of the trigeminal nerve, including PRF treatment of the infraorbital nerve and mental nerve, could significantly improve the symptoms of neuralgia. [11][12][13][14] However, evidence for the treatment of supraorbital neuralgia using PRF is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that the efficacy of PRF treatment was positively correlated with the output voltage [35]. Subsequently, prospective, randomized, double-blinded studies have certified that high-voltage PRF is more effective than standard-voltage in treating idiopathic TN and refractory infraorbital neuralgia [33,36]. However, there is a lack of research evaluating the effectiveness and safety of high-voltage PRF on the treatment of idiopathic GPN patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, a randomized controlled study showed that high voltage PRF of Gasserian ganglion significantly improved the treatment outcomes relative to standard voltage PRF in patients with trigeminal neuralgia (9). However, whether increasing the output voltage of PRF can improve the treatment outcomes of neuralgia of the infraorbital nerve is unknown.…”
Section: Operationmentioning
confidence: 99%
“…For the standard voltage group, the automatic PRF mode was used (standard parameters: 42 o , 2 Hz, 120 s, 2 times). For the high voltage group, the manual PRF mode was used (maximum temperature: 42 o ; the UP knob was turned to increase the output voltage until the maximum voltage [bearable without causing pain in conscious patients] was reached; 120 s, 2 times) (9). At one month after treatment, patients who did not respond to the PRF received RFTC; the same puncture procedure was performed, and the RFTC mode was used (…”
Section: Wwwpainphysicianjournalcommentioning
confidence: 99%